Peran Tenaga Kefarmasian dalam Penanggulangan Tuberkulosis (TBC) - Chusun Chusun; Indrianti poppy; Nabila Nuha (Jurnal Abdi Masyarakat Kita, 2022)
Tuberculosis caused by Mycobacterium tuberculosis is a chronic disease, where the key to successful treatment is patient compliance. The estimated TB case in Indonesia in 2020 is 845,000 (eight hundred and forty five thousand) which is the second largest case in the world after India.The purpose of this webinar is to assist government programs in TB control and at the same time to remind that the active role of pharmacists is needed by the community / sufferers.The webinar was attended by 207 participants, of which 88.4% were women and 11.6% were men. Most of the participants (68.1%) were between 20 – 30 years old. The material is delivered through power point media.In the question and answer session/ discussion, some of the questions were theoretical in nature, this is probably because most of the participants were graduates of Diploma Three in Pharmacy, maybe even still students. Another factor that caused the participants to be less enthusiastic about asking questions was the role of pharmacists or perhaps the pharmaceutical technical personnel themselves in the TB control team, generally only as team members.At the end of the session participants were asked to fill out a post test and evaluation questionnaire via google form, but there were still 53.6% of participants who did not understand that drug counseling could be done via telepharmacy and 31.4% did not know about the BCG immunization program in infants. Evaluation of participant satisfaction is assessed from the average percentage of the number of answers stating "very good" and "good", which is 97.65% of participants stating they are satisfied.The activity evaluation questionnaire was tested for validity and declared valid because all questions were greater than r table, namely 0.3120, with a significance of 0.05. The reliability test also shows a reliable questionnaire which can be seen from the Cronbach's Alpha value which is greater than the constant value, which is 0.916. The constant value is 0.600.